2011
DOI: 10.1017/s002211201000635x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between two spherical bubbles rising in a viscous liquid

Abstract: The three-dimensional flow around two spherical bubbles moving in a viscous fluid is studied numerically by solving the full Navier–Stokes equations. The study considers the interaction between two bubbles for moderate Reynolds numbers (50 ≤ Re ≤ 500, Re being based on the bubble diameter) and for positions described by the separation S (2.5 ≤ S ≤ 10, S being the distance between the bubble centres normalised by the bubble radius) and the angle θ (0° ≤ θ ≤ 90°) formed between the centreline and the direction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
68
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 41 publications
11
68
2
Order By: Relevance
“…Experimentally, an unstable equilibrium distance can indeed be found for clean bubbles which preserve its spherical shape as increasing the Re number (i.e., rising in silicone oils) [24]. Such equilibrium distance, which has been numerically found to be dependent on the Re number [23,25], is unstable in the sense that bubbles often escape from the vertical line.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Experimentally, an unstable equilibrium distance can indeed be found for clean bubbles which preserve its spherical shape as increasing the Re number (i.e., rising in silicone oils) [24]. Such equilibrium distance, which has been numerically found to be dependent on the Re number [23,25], is unstable in the sense that bubbles often escape from the vertical line.…”
Section: Introductionmentioning
confidence: 89%
“…Several experimental and numerical studies of the interaction of two bubbles at intermediate Re numbers have been devoted to the construction of the bridge that joins the creeping and potential flows [13,[25][26][27]8,9]. These studies have revealed that two bubbles rising in-line follow the viscous dominated flow behavior at least up to a Reynolds number of O(1 0 0), i.e., the trailing bubble approximating the leading one.…”
Section: Introductionmentioning
confidence: 99%
“…In short, it could slide at constant speed or repeatedly bounce with a constant mean velocity. We characterize this final state considering also the Reynolds and Weber numbers but using the wall velocity V w such that Re w = Re term V w /V term and We w = We term (V w /V term ) 2 . The ratio V w /V term is determined experimentally.…”
Section: Methodsmentioning
confidence: 99%
“…Significant advances have been reached in recent years due to the mature understanding of the hydrodynamic forces that affect the motion of single bubbles ascending in Newtonian liquids [1]. There is a clear understanding of the effects of viscous and inertial forces around interacting bubbles [2]. Conversely, despite their omnipresence, the understanding of wall effects is still modest.…”
Section: Introductionmentioning
confidence: 99%
“…During the collision, the leading droplet will induce a wake which will effect the drag force acting on the trailing droplet [24]. Depending on the magnitude of the absolute velocities of the droplets and the collision angle, the wake effect can cause a net attraction or repulsion of the droplets [25]. The magnitude of the effect increases with decreasing h. Further, as the droplets are subjected to shear flow, droplet deformation during the collision can be expected to be asymmetrical.…”
Section: Evaluation Of the Film Drainage Profiles And Coalescence Timesmentioning
confidence: 99%